Evaluating the effectiveness and safety of a novel phage cocktail as a biocontrol of Salmonella in biofilm, food products, and broiler chicken - Torkashvand, Narges; Kamyab, Haniyeh; Aarabi, Parisa; Shahverdi, Ahmad Reza; Torshizi, Mohammad Amir Karimi; Khoshayand, Mohammad Reza; Sepehrizadeh, Zargham (Frontiers in Microbiology, 2024)
Salmonella is a foodborne pathogen of animal and public health significance. Considering the disadvantages of antibiotics or chemical preservatives traditionally used to eliminate this pathogen, attention has shifted, in recent years, toward biocontrol agents such as bacteriophages, used either separately or in combination to prevent food contamination. However, extensive use of phage-based biocontrol agents in the food industry requires further studies to ensure their safety and efficacy. In the present study, we investigated the effectiveness and safety of phage cocktail, a phage cocktail comprising three pre-characterized Salmonella phages (vB_SenS_TUMS_E4, vB_SenS_TUMS_E15 and vB_SenS_TUMS_E19). First, we performed an MTT [3-(4,5-dimethylthiazol-2-yl)-2,5 diphenyl tetrazolium bromide] assay on a human foreskin fibroblast cell line, in which the resulting high cell viability revealed the safety of the phage cocktail. Next, we performed a time-kill assay in which a 4 Log decline in bacterial levels was detected. Additionally, we utilized a colorimetric method to evaluate the anti-biofilm activity of phage cocktail, in which it proved more efficacious compared to the MIC and MBEC levels of the antibiotic control. Then, we assessed the ability of phage cocktail to eradicate Salmonella in different food samples, where it considerably reduced the bacterial count regardless of the temperature (4°C and 25°C). Lastly, we used broiler chickens as an animal model to measure the growth-promoting activity of phage cocktail. Salmonella-infected chickens orally treated with modified phage cocktail demonstrated no mortality and a significant increase in weight gain compared to the untreated group (p ≤ 0.0002). The study presents a novel research evaluating the effectiveness and safety of a phage cocktail as a biocontrol agent against Salmonella in various contexts, including biofilms, food products, and broiler chickens. This multifaceted approach underscores the promising role of phage therapy as a sustainable biocontrol strategy in food safety and public health contexts.